Parametric optimization of a flexure-based active Gurney flap mechanism for minimum stress - Freire Gómez, J.; Booker, J.D.; Mellor, P.H. (My University, 2015)
The EU's Green Rotorcraft programme is pursuing the development of a functional and airworthy Active Gurney Flap (AGF) for a full-scale helicopter rotor blade. Interest in the development of this ‘smart adaptive rotor blade' technology lies in its potential to provide a number of aerodynamic benefits, which would in turn translate into a reduction in fuel consumption and noise levels. The AGF concept under development was selected following a design methodology presented in a previous publication and is characterized by the employment of crossed flexure pivots, which provide important advantages over bearings as they are not susceptible to seizing and do not require any maintenance (i.e. lubrication or cleaning). A baseline design of said mechanism was successfully tested both in a fatigue rig and in a 2D wind tunnel environment at flight-representative deployment schedules. However, finite element analysis of the baseline design under full in-flight centrifugal accelerations, aerodynamic loads and blade deformations shows that the stresses arising on the flexures would compromise their mechanical integrity. This paper investigates the potential to reduce the stresses on the flexures through parametric optimization of the baseline design. To this end, a procedure combining a simplified finite element model of the mechanism and an optimization algorithm is employed. From all the parameters required to fully define the mechanism, only those deemed to be the most influential were taken as optimization variables. The optimization approach adopted manages to reduce the stress on all flexures to levels below the yield stress, yet not enough so as to fulfil the design requirements in terms of safety margin and fatigue life. Future work will assess the scope for further stress reduction by altering additional design parameters.
Keywords: Green Rotorcraft